Unraveling the role of cellular phosphatases in lysosome function and storage diseases - Kumari, Darpan; Advised by Setty, Subba Rao G (Bangalore : Indian Institute of Science, 2024)
Investigating the role of DUSP14 and Rab7A in endo-lysosomal trafficking in mammalian cells Eukaryotic cells maintain homeostasis and interact with their environment through intricate metabolic processes, including the endo-lysosomal pathways that occur within membrane-bound organelles and the cytosol. This pathway consists of a dynamic network of compartments: early/sorting endosomes (E/SE), recycling endosomes (RE), late endosomes (LE), and lysosomes. Lysosomes play a vital role in degrading various intracellular and extracellular materials obtained via autophagy and endocytosis, facilitating the recycling of macromolecules. Lysosomes receives proteins accurately through endocytic pathways involving sorting signals and post-translational modifications. Protein phosphorylation, one of the post-translational modifications, regulates various cargo trafficking steps, for example, the addition of mannose-6-phosphate to nascent lysosomal hydrolases occurs after their transport from the ER to the Golgi. Recent studies using RNAi screen from our lab identified novel phosphatases whose knockdown enhances lysosomal function, particularly in Gaucher disease. Objective I: Characterizing the role of DUSP14 in the endo-lysosomal trafficking pathways. DUSP14 is recognized for its role in dephosphorylating MAP kinases and is important in tissue injury and cellular signalling. Previous RNAi screens indicated that DUSP14 knockdown increases gb(B-GC activity in lysosomes, but its specific role in endo-lysosomal trafficking remains unclear. Initial immunoblotting and immunofluorescence microscopy revealed DUSP14 expression in HeLa cells. We knocked down DUSP14 using siRNA, leading to altered lysosomal distribution characterized by the aggregation of late endosomes and lysosomes at the cell periphery. While LysoTracker staining showed no significant changes in acidity, DQ-BSA activity assays indicated enhanced proteolytic activity in DUSP14-depleted cells, suggesting a potential role for DUSP14 in lysosomal positioning and function. Additionally, altered distributions of lysosomal hydrolase receptors M6PR and LIMP2 were observed, suggesting DUSP14's involvement in receptor recycling. Notably, DUSP14 knockdown affected microtubule-dependent lysosomal aggregation, disrupted recycling pathways indicated by Rab11A. Additionally, we observed dispersion of AP1 adaptor, the coat protein clathrin and GRASP55 localization from the TGN in DUSP14 depleted cells. Further studies are needed to clarify DUSP14's mechanisms in lysosome positioning and post-Golgi transport. Overall, our research offers initial insights into DUSP14's influence on lysosomal dynamics. Objective II: Unravelling the role of Rab7A in regulating the recycling endosome dynamics. Rabs, a family of small GTPases, act as key regulators of vesicular transport, cycling between inactive and active states. Recycling endosomes (REs) are crucial intermediates that primarily recycle cargo from endosomes to the cell surface. Rab7A, mainly found in late endosomes and lysosomes, facilitates cargo transport between these compartments by interacting with specific effectors and motor proteins, enabling both retrograde and anterograde lysosomal movement. However, its role in regulating the dynamics of REs has been underexplored. We overexpressed wild-type Rab7A (Rab7AWT) and a dominant negative mutant (Rab7AT22N) in HeLa cells to study RE dynamics using KIF13A, Rab22A, and STX13 as markers. Notably, overexpression of Rab7AT22N and knockdown resulted in the loss of RE tubules. Further analysis revealed that Rab7A knockdown reduced localization of key cargos at the cell periphery and disrupted Rab11 tubules, suggesting Rab7A$1 (Bs involvement in regulating recycling pathways. Immunoblotting indicated decreased levels of Rab22A and Rab11 in Rab7A-depleted cells, highlighting its potential role in these pathways. Further investigation is needed to elucidate Rab7A$1 (Bs mechanisms in RE dynamics.s
Includes bibliographical references.
PhD;2024;Microbiology and Cell Biology.
Keywords: Lysosomes; DUSP14; Rab7